Pair-copula constructions for financial applications: A review - Kjersti Aas (Econometrics, 2016)
This survey reviews the large and growing literature on the use of pair-copula constructions (PCCs) in financial applications. Using a PCC, multivariate data that exhibit complex patterns of dependence can be modeled using bivariate copulae as simple building blocks. Hence, this model represents a very flexible way of constructing higher-dimensional copulae. In this paper, we survey inference methods and goodness-of-fit tests for such models, as well as empirical applications of the PCCs in finance and economics.
Keywords: C13; C15; C51; C52; C53; C58; 330; pair-copula constructions; vines; dependence; conditional distribution; flexibility